Components interactions controlling starch–kaolinite composite films properties. (6th March 2015) - Mbey, J.A.; Thomas, F.
Highlights: Cassava starch and kaolinite properties. Origins and intensities of interactions. Interfacial interactions related to starch–kaolinite composite films properties. Abstract: In order to relate the primary filler–matrix interactions to the macroscopic properties of starch–kaolinite composite material, these interactions are monitored through homo- or hetero-coagulation experiments involving both components. Turbidity measurement and Infrared spectra confirm the extreme weakness of the interactions. The addition of calcium cations shows that these weak interactions between starch and kaolinite are due to the combination of the electrostatic repulsion and hydrogen bonds formation between this two negatively charge components. Some possible relationships between the starch–kaolinite interactions and starch–kaolinite composite films properties are proposed.